2010
DOI: 10.25011/cim.v33i6.14589
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection is associated with reduced serum alpha-1-antitrypsin concentrations

Abstract: Purpose: Several observations suggest the presence of HIV-suppressive factors in the fluid phase of blood. Alpha-1-antitrypsin (AAT), the most abundant serine protease inhibitor in the circulation, has potent anti-HIV activity in vitro, and may function as an endogenous HIV suppressor. Therefore, we assessed serum AAT concentrations for association with HIV infection. Methods: In this cross-sectional study, serum AAT concentrations were measured in 66 persons with HIV infection and in 45 healthy persons (Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
3
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 16 publications
(20 reference statements)
0
33
3
1
Order By: Relevance
“…Low a 1 -antitrypsin levels have been associated with HIV infection and elevated plasma sCD14 levels. 41,42 To assess emphysema severity, we used a validated, semiquantitative approach. 5,7,43 Consistent with other studies, CT scans were scored by a single radiologist.…”
Section: Discussionmentioning
confidence: 99%
“…Low a 1 -antitrypsin levels have been associated with HIV infection and elevated plasma sCD14 levels. 41,42 To assess emphysema severity, we used a validated, semiquantitative approach. 5,7,43 Consistent with other studies, CT scans were scored by a single radiologist.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a screening study of ultra-filtered human plasma and protein sequencing revealed that, indeed, the major plasma-derived inhibitor of HIV-1 is circulating human AAT (51). Accordingly, it was later demonstrated that HIV-1 infection is associated with reduced serum AAT concentrations (52). A C-terminal 26-residue peptide fragment of AAT, the result of internalized and cleaved AAT, was found to be a direct inhibitor of viral infection (53).…”
Section: Binding Targets That Are Unrelated To Protease Inhibitionmentioning
confidence: 99%
“…It may play a role as an endogenous HIV suppressor. The diminished circulating alpha-1-antitrypsin concentration observed in HIV infection is consistent with a role as an endogenous HIV suppressor (Bryan et al 2010).…”
Section: Trypsin Inhibitorsmentioning
confidence: 54%